2020
DOI: 10.24036/perspektif.v3i2.258
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Penelitianaini dilatarbelakangi oleh ketertarikanapeneliti melihatamahasiswa Papua yang berada di Universitas Negeri Padang (UNP) yang unik dan berbeda dengan mahasiswa mayoritas di UNP. Tujuanapenelitianainiaadalahauntukamengetahuiaprosesaadaptasi mahasiswaaasalaPapua di UNP dengan program pendidikan adik. Kemudian hasilatemuan peneliti tersebut dianalisis denganamenggunakanateoriastrukturalafungsionalaolehaTalcot Parsons denganakonsep AGIL. Penelitian ini menggunakan pendekatan kualitatif dengan tipe penelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The experience of the agriculture extension also has a significant positive effect on the performance level [20]. This is supported by the research of Talisman [23] who reported that experience plays a significant role in a person's performance. According to [20] farmers tend to have more confidence in extension workers who have long working experience compared to those who are fresh graduate.…”
Section: Characteristics Of Respondentsmentioning
confidence: 54%
“…The experience of the agriculture extension also has a significant positive effect on the performance level [20]. This is supported by the research of Talisman [23] who reported that experience plays a significant role in a person's performance. According to [20] farmers tend to have more confidence in extension workers who have long working experience compared to those who are fresh graduate.…”
Section: Characteristics Of Respondentsmentioning
confidence: 54%